The spider Micrathena shealsi Chickering, 1960 (Araneae, Araneidae): description of the male, with new data on its geographic distribution - Argañaraz, Carina I.; Rubio, Gonzalo D. (Zootaxa, 2011)
The male of Micrathena shealsi Chickering, 1960 is described and illustrated for the first time. New geographic records of this species are provided, revealing that M. shealsi inhabits the higher altitudinal belts (1000–3000 m) of the Yungas ecoregion (mountain forests and rainforests from Argentina). Male specimens were observed in the same web of females, in most cases on the upper periphery hanging by a silk line.